The Correlation between Madrasah Diniyah Takmiliyah Wustha Program Implementation and Student Commendable Moral Development at State Junior High School 1 Rambah Rokan Hulu Regency - Anandita Yahya Anan; Ana Citra Annisa (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This research aimed at knowing the correlation between Madrasah Diniyah Takmiliyah Wustha program implementation and student commendable moral development at State Junior High School 1 Rambah, Rokan Hulu Regency. The correlation between Madrasah Diniyah Takmiliyah Wustha program implementation and student commendable moral development showed that the better Madrasah Diniyah Takmiliyah Wustha program implementation was, the better student commendable moral development would be. Questionnaire, interview, and documentation were the instruments of this research. The subjects of this research were 3 teachers of Madrasah Diniyah Takmiliyah Wustha at State Junior High School 1 Rambah, Rokan Hulu Regency, and 72 students—38 of the seventh-grade students and 34 of the eighth-grade students. The obtained data were analyzed by using product moment correlation technique. Based on the research findings, there was a strong correlation between Madrasah Diniyah Takmiliyah Wustha program implementation and student commendable moral development at State Junior High School 1 Rambah, Rokan Hulu Regency with the coefficient of correlation 0.633, and it was on the range of 0.60-0.799.